Serum Urate in Chronic Gout — Will It Be the First Validated Soluble Biomarker in Rheumatology? - STAMP, LISA K. (2011)
OBJECTIVE: To summarize evidence for and endorsement of serum urate (SU) as having fulfilled the OMERACT filter as a soluble biomarker in chronic gout at the 2010 Outcome Measures in Rheumatology Meeting (OMERACT 10). METHODS: Data were presented to support the use of SU as a soluble biomarker in chronic gout and specifically the ability to utilize it to predict future patient-reported outcomes. RESULTS: SU was accepted as having fulfilled the OMERACT filter by 78% of voters. However, consensus was not obtained regarding its use as a soluble biomarker in chronic gout. Although the majority of the criteria for a soluble biomarker were fulfilled, the key criterion of association of the biomarker with outcomes was not agreed upon. It was agreed that the appropriate choice of endpoint must be linked to its clinical importance to the individual with the disorder and its temporal relationship to the intervention. Appropriate outcomes in chronic gout may therefore include gout flares, reduction in tophi, and patient-reported outcomes. CONCLUSION: SU is a critical outcome measure. It has the potential to fulfil criteria for a soluble biomarker. Further analyses of existing data from randomized controlled trials will be required to determine whether SU can predict future important outcomes, in particular disability.